The Effect of Chinese Traditional Exercise-Baduanjin on Physical and Psychological Well-Being of College Students: A Randomized Controlled Trial - Li, Moyi (PLoS One, 2015)
BACKGROUND: The physical and mental health of college students tends to continuously decline around the world, therefore, it is important to improve their health during college period. Baduanjin, a traditional Chinese exercise which combines movements with breath and mind, may be one of the selectable effective exercises. However, the effect of Baduanjin exercise on college students has not been established. In this study, we systematically assessed the effectiveness and safety of Baduanjin exercise on physical and mental health of college students by a rigorous randomized, parallel-controlled design. METHODS: A total of 222 college students from Fujian University of Traditional Chinese Medicine were recruited and randomly allocated at an equal ratio into control or Baduanjin training. Participants in control group were informed to maintain their original activity habit, and those in Baduanjin exercise group received a 12-week Baduanjin exercise training with a frequency of 1 hour per day and 5 days per week on the basis of their original activity habit. The physical and psychological outcomes, including lumbar muscle strength, lower limb proprioception function, physical fitness, as well as self-reported symptom intensity, stress, self-esteem, mood, quality of life, quality of sleep, and adverse events, were evaluated at baseline, 13 weeks (at the end of 12-week intervention), and 25 weeks (after the 12-week follow-up period). Intention-to-treat analysis was performed for the above outcomes. RESULTS: Compared with controls, significant improvements in Baduanjin exercise group at the end of 12-week intervention period were found on lower limb proprioception function (the rate of average trace error on right lower limb (%): control 23.50±5.50, Baduanjin 21.92±6.54, P=0.004; the rate of average trace error on left lower limb (%): control 22.32±6.62, Baduanjin 20.63±4.62, P=0.046), cardiorespiratory endurance (step test index: control 47.66±5.94, Baduanjin 50.07±9.30, P=0.025), flexibility (control 14.35±7.26cm, Baduanjin 15.39±6.43cm, P=0.009) and explosive force of lower limb (standing long jump test (m): control 1.77±0.24, Baduanjin 1.79±0.22, P=0.005 for adjustment baseline) in physical outcomes, and attention (Schulte Grid test (second): control 210.4±51.15, Baduanjin 192.4±47.14, P=0.034) in mental outcome. Lumbar muscle strength in Baduanjin group had been moderately enhanced but no significant difference compared to controls. No significant changes in other physical and mental outcomes, including vital capacity, blood pressure, heart rate, hand grip force, self-symptom intensity, stress, self-efficacy, quality of life, and quality of sleep, were found between groups. No adverse event was reported during the study period. CONCLUSION: Regular Baduanjin exercise had an advantage for college students on improvement of lower limb proprioception, enhance of cardiorespiratory endurance, flexibility, explosive force of lower limb and attention, compared with usual exercise. TRIAL REGISTRATION: Chinese Clinical Trial Registry ChiCTR-TRC-13003329 http://www.chictr.org